The macroeconomics of pension reform: The case of severance pay reform in Italy - Sergio Cesaratto (Intervention. European Journal of Economics and Economic Policies, 2011)
In the last two decades Italy implemented a number of reforms of the public pay-as-you-go (PAYG) scheme that curtailed future pensions. Governments therefore felt the need to increase the number of workers contributing to fully funded (FF) schemes to offset the expected fall in public pensions. In the private sector an existing saving fund, the severance pay scheme (Trattamento di fine rapporto or TFR) was used to expand the anaemic existing FF pillar. The macroeconomic content of the reform seems fragile since the economy's amount of precautionary saving has not changed. The question is why a bolder reform aiming at creating an additional new old-age saving scheme has not been attempted by the Italian Government. The answer presumably has to do with troubles surrounding the macroeconomics of pension reforms, in particular the difficulties of setting up a FF scheme from scratch or by diverting resources from an existing PAYG program. Not surprisingly, no reform was attempted in the public sector where the TFR works on a PAYG basis. An ancillary argument to defend the reform relies on presumed higher returns from private pension funds (PFs) compared to the old TFR. In this light, the paper examines the non-exiting financial performance of the PFs. The instability of financial markets, even before the current crises, and the fondness of workers for the old TFR are finally used to explain the low popularity of the reform. All in all, the reform seems to be more in the nature of political window-dressing, consisting in a change in management of an existing saving fund, in order to show that something has been done to preserve the future standard of living of retirees.
Keywords: E11; G23; H55; 330; pension reforms; Sraffian theory; Italy